Síntesis y crítica de las evaluaciones de la efectividad de los motores de búsqueda en la Web. (Synthesis and critical review of evaluations of the effectiveness of Web search engines) - Francisco Javier Martínez Méndez; José Vicente Rodríguez Muñoz (Information Research: An International Electronic Journal)
A considerable number of proposals for measuring the effectiveness of information retrieval systems have been made since the early days of such systems. The consolidation of the World Wide Web as the paradigmatic method for developing the Information Society, and the continuous multiplication of the number of documents published in this environment, has led to the implementation of the most advanced, and extensive information retrieval systems, in the shape of web search engines. Nevertheless, there is an underlying concern about the effectiveness of these systems, especially when they usually present, in response to a question, many documents with little relevance to the users' information needs. The evaluation of these systems has been, up to now, dispersed and various. The scattering is due to the lack of uniformity in the criteria used in evaluation, and this disparity derives from their a periodicity and variable coverage. In this review, we identify three groups of studies: explicit evaluations, experimental evaluations and, more recently, several proposals for the establishment of a global framework to evaluate these systems.